Efficacy, safety and predictive factors for outcomes and adverse events in sclerotherapy for venous malformations in children - Schmitt, Niclas; Lorenz, Julia; Wucherpfennig, Lena; Karimian-Jazi, Kianush; Ruping, Fabian; Ristow, Oliver; Hoffmann, Jürgen; Günther, Patrick; Bendszus, Martin; Möhlenbruch, Markus Alfred; Vollherbst, Dominik (Journal of pediatric surgery, 2026)
Objectives - Percutaneous sclerotherapy is an established treatment for venous malformations (VM), while data on its use in children remain limited. This study aimed to evaluate the efficacy, safety and predictors of clinical outcome and adverse events (AEs) in children undergoing polidocanol-based sclerotherapy of VMs. - Methods - A retrospective single-center analysis was conducted, including children with VMs treated with polidocanol sclerotherapy. Demographics, clinical, and radiological data were analyzed, and multivariate logistic regression was used to assess the influence of patient- and VM-related factors on clinical outcomes and AEs. - Results - 83 children (182 treatment sessions) were included. Symptom improvement was observed in 54.0 %, while 34.9 % had stable symptoms and 11.1 % reported worsening (mean follow-up: 0.81 ± 1.22 years). The overall AE rate was 13.3 %, with mild but permanent sequela in 3.6 %. Multivariate analysis identified VMs of the extremities as a significant predictor for AEs (p < 0.01; complication rate: 12.0 % versus 1.2 % in other locations). No factor influencing clinical outcome was found (p = 0.11). We observed clinical improvement in most cases (54.0 %), despite a mean VM size increase of 7.76 ± 33.64 % after polidocanol-based sclerotherapy. - Conclusion - Polidocanol-based sclerotherapy is an effective and safe treatment option for pediatric VMs. Complications are more common in VMs of the extremities due to higher mobility and hypostatic pressure. Notably, despite therapeutic size reduction is often limited, clinical improvement, such as pain relief, can often be achieved, which needs to be considered for treatment planning.
Online verfügbar 24 October 2025, Version des Artikels 4 November 2025
Gesehen am 16.02.2026